2020
DOI: 10.1038/s41396-020-00763-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial interactions in the mosquito gut determine Serratia colonization and blood-feeding propensity

Abstract: How microbe–microbe interactions dictate microbial complexity in the mosquito gut is unclear. Previously we found that, Serratia, a gut symbiont that alters vector competence and is being considered for vector control, poorly colonized Aedes aegypti yet was abundant in Culex quinquefasciatus reared under identical conditions. To investigate the incompatibility between Serratia and Ae. aegypti, we characterized two distinct strains of Serratia marcescens from Cx. quinquefasciatus and examined their ability to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 144 publications
7
65
1
Order By: Relevance
“…Indeed, colonization resistance assays using gnotobiotic mosquitoes (i.e., mosquitoes with a known initial microbiota composition) showed that the initial microbiota impacts the colonization efficiency of other S. marcescens strains in Ae. aegypti ( Kozlova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, colonization resistance assays using gnotobiotic mosquitoes (i.e., mosquitoes with a known initial microbiota composition) showed that the initial microbiota impacts the colonization efficiency of other S. marcescens strains in Ae. aegypti ( Kozlova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the infection of mosquitoes with the pathogenic fungus Beauveria bassiana causes microbiome dysbiosis and over-proliferation and translocation of Serratia marcescens from the gut to the hemocoel, eventually killing the insect [134]. Microbes can benefit from each other, like symbiotic bacteria and yeast in Drosophila [135], but they can also exclude one another, like Enterobacteriaceae and Serratia [136] or Asaia and Wolbachia [137] in mosquitoes. In flies and mosquitoes, microbiota interactions with Wolbachia occur but these do not influence the ability of Wolbachia to block pathogens [138,139].…”
Section: Microbe-microbe Interactionsmentioning
confidence: 99%
“…Feeding behaviour is disrupted in Ae. aegypti by Serratia [ 136 ] and in Anopheles mosquitoes when exposed to heat-killed E. coli [ 154 ] or Chromobacterium [ 155 ]. Microbiota also have the potential to affect host-seeking behaviour through modulation of their chemosensory system.…”
Section: Influence Of Microbiota On Vector Biting Rate (A)mentioning
confidence: 99%
“…The genome of S. marcescens encodes several genes for heme uptake and storage, as well as demonstrating alpha-hemolytic activity, i.e., the complete lysis of blood cells ( Chen et al, 2017 ). Yet, fewer females infected with S. marcescens took blood meals in comparison with their uninfected cohorts ( Kozlova et al, 2021 ).…”
Section: A Path Forward: a Most Wanted List For Microbes In Gnotobiotic Studiesmentioning
confidence: 99%